Taxonomic notes on the genera Scatella and Scatophila (Diptera: Ephydridae) with a remark on Trixoscelis chilensis (Trixoscelididae) - Zatwarnicki, Tadeusz; Irwin, Anthony G. (Zootaxa, 2018)
Two new combinations are proposed in Scatella for Ephydra australis Walker, 1853 and Opomyza guttata Macquart, 1843. Two species are resurrected from synonymy: Scatella lacustris (Meigen, 1830), revised status and Trixoscelis chilensis (Schiner, 1868), revised status (Trixoscelididae). Nine new synonyms are suggested: Scatella insularis Mathis & Wirth, 1981 = S. australis (Walker, 1853); S. lutosa nigripes Oldenberg, 1923 = S. obsoleta Loew, 1861; S. septempunctata Malloch, 1933 = S. gratiellae Canzoneri & Raffone, 1987 = S. septemfenestrata Lamb, 1912; S. tenuicosta Collin, 1930 = S. lacustris (Meigen, 1830); S. vulgata Cresson, 1931 = S. guttata (Macquart, 1843); Scatophila zlobini Krivosheina, 2009 = S. hirtirostris Sturtevant and Wheeler, 1954; S. grisescens Frey, 1915 = S. mesogramma (Loew, 1869); S. planiceps (Boheman, 1853) = S. quadriguttata (Meigen, 1830).